2021
DOI: 10.1186/s13731-021-00190-4
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion and development in the least developed countries in Asia and Africa

Abstract: The purpose of this paper is to investigate the relationship between the financial inclusion index and development variables in the least developed countries in Asia and Africa by using annual data of 42 countries for the period 2000–2019. The pooled panel regression and panel data analysis technique are used to explore this relationship. The empirical finding indicates that economic growth leads to financial inclusion. Unemployment and literacy rates are among the factors contributing to financial inclusion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 41 publications
3
35
0
Order By: Relevance
“…Alternatively, completing secondary and tertiary education levels have a positive significant relationship with financial inclusion-gender equality. In line with previous studies, advanced education levels increase financial inclusion-equality based index (Arora, 2012;Cicchiello, Kazemikhasragh, Monferrá, et al, 2021;Mouna & Jarboui, 2021;Yan & Qi, 2021). The results with the interaction of Covid-19 restrictions show that all education levels increase financial inclusion in Latin American countries.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Alternatively, completing secondary and tertiary education levels have a positive significant relationship with financial inclusion-gender equality. In line with previous studies, advanced education levels increase financial inclusion-equality based index (Arora, 2012;Cicchiello, Kazemikhasragh, Monferrá, et al, 2021;Mouna & Jarboui, 2021;Yan & Qi, 2021). The results with the interaction of Covid-19 restrictions show that all education levels increase financial inclusion in Latin American countries.…”
Section: Resultssupporting
confidence: 91%
“…Taking into account the research of Cicchiello et al. (2021) and wanting to analyze and determine the extent of financial inclusion in Latin America and the Caribbean, we employed the following pooled‐panel OLS model:Xitalicit=α+βAitalicit+εi,where X represents the financial inclusion‐based gender equality index, i represents the country dimensions, t represents year, A represents the independent variables, and ε i represents the error term.…”
Section: Modelmentioning
confidence: 99%
“…Mindra et al (2017) postulated that women’s self-efficacy is a significant factor for women’s financial inclusion. Literacy is one of the significant contributors towards greater financial access but women are behind men in attaining literacy which leads to the gender gap in financial inclusion in developing countries (Cicchiello et al, 2021). Sabherwal et al (2019) also attribute low access to information and lack of financial literacy as factors constraining financial inclusion of women.…”
Section: Resultsmentioning
confidence: 99%
“…Omar and Inaba (2020)'s analysis for the economies of 116 developing countries consisting of Asia, Africa, Latin America and the Caribbean showed that financial inclusion significantly reduced poverty and income inequality in these countries. In another recent analysis conducted by Cicchiello et al (2021), for the least developed 42 countries in Asia and Africa, findings were obtained that low financial access reduces economic development.…”
Section: Financial Inclusionmentioning
confidence: 99%